IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY BANK CENTRAL ASIA (BCA) DALAM PROGRAM SOLUSI SINERGI GUNA MENDUKUNG PENGEMBANGAN MASYARAKAT INDONESIA - Mayasari, Silvina (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
This study aims to see how the Implementation of Bank Central Asia's Corporate Social Responsibility (BCA) in Improving the Welfare of the Indonesian Society. Corporate Social Responsibility is defined as the company's responsibility to stakeholders to act ethically, minimize negative impacts and maximize positive impacts which include economic, social and environmental aspects (triple bottom line) in order to achieve sustainable development goals. . The research method in this study is a descriptive qualitative method that focuses on the Implementation of Bank Central Asia's (BCA) Corporate Social Responsibility in Improving the Welfare of the Indonesian Society. Data Collection Techniques Data collection techniques in qualitative research are observation, literature and documentation studies. In this CSR program, BCA through Synergy Solutions with its 4 CSR programs is carried out in partnership with various parties focusing on several activities implemented to help the government improve the development of Indonesian society, through the Cultural Preservation program, Empathy Program, Health Improvement and Environment Preservation. In practice, BCA collaborates with various parties who are competent in their respective fields, such as the TNI, WWF Indonesia, the Indonesian Ophthalmologist's Association, Media Clinic and various other social institutions.